Zitterbewegung near new Dirac points in graphene superlattices. (6th September 2018) - Luan, Jianli; Li, Shangyang; Ma, Tianxing; Wang, Li-Gang
Abstract: New Dirac points may appear when periodic potentials are applied to graphene, and there are many interesting effects near them. Here we investigate the Zitterbewegung effect of fermions described by a Gaussian wave packet in graphene superlattice near these points. The Zitterbewegung near different Dirac points has similar characteristics, while fermions near new ones have different group velocities in both x - and y -direction, which causes the different properties of the Zitterbewegung near them. We also investigate the Zitterbewegung effect influenced by multi Dirac points, and get the evolution with changing potential. Our results suggest that graphene superlattice may provide an appropriate system to study the Zitterbewegung effect near new Dirac points experimentally.